The impact of economic factors on the change in the structure of Polish households expenditure - use of Markov chains - Katarzyna Osiecka (Institute of Economic Research (IER), 2017)
Research background: Polish economy for several years which is a subject to continuous transformation, has a close relationship with three overlapping during the process: the transformation of the economy, Polish integration with the European Union and globalization. All these processes are mutually penetrate and carry consequences for the development of the most important economic indicators. Purpose of the article: The changing of social and economic conditions which households face always influence their important choises on both the expenditure and raise money, behavior in the surrounding reality, shaping their needs and expectations with respect to the purchased products and services. By the fact that consumption behavior are subject to constant changes and fluctuations, they must be under continuous observation and confrontation with determinants that determine these changes. The most important factor in these changes is the income available to households, as well as the rate of price increases, or the savings rate. Methodology/methods: The assumption that the structure of household expenditure is subject to change according to the mechanism described by Markov chain is difficult to interpret in this point of view. However, the lack of a clear interpretation of the process does not interfere with the usage of Markov chains to study the structure of changes. Findings: The impact of these characteristics of the economic and financial changes in the structure of household expenditure is reduced to the study of heterogeneous chains, in which the elements of the matrix of transition probabilities are defined by the functions of these characteristics and treated as variables.
Keywords: D14; 330; consumption; structure of expenditure; households expenditure; Markov's chains